Human-AI Symbiosis: Unveiling the Inherent Limitations of AI through the Sadharanikaran Model of Communication - Lama Yolmo, Ugyal T.; Basnett, Pooja (Bodhi: An Interdisciplinary Journal, 2024)
In the unending discourse surrounding the potential replacement of humans by artificial intelligence (AI) in the future, this paper introduces a distinctive perspective grounded in the belief that such a substitution is implausible. It asserts that the invaluable intricacies of human communication, essential for fostering genuine connections, remain beyond the grasp of AI. Employing Adhikary’s Sadharanikaran Model of Communication (SMC) as the guiding framework, this article embarks on a methodical exploration of human communication, dissecting the nuanced components that contribute to its depth and richness. Through empirical evidence and comparative analyses, it sheds light on the inherent limitations of AI, providing a comprehensive understanding of why the SMC reinforces the irreplaceable role of humans in communication. By scrutinizing instances where human communication transcends mere information exchange, it is argued that the qualitative dimensions of human interaction defy replication by AI. Furthermore, a comparative analysis of AI-driven communication and human discourse also has been presented. Rather than positioning AI as a substitute, the emphasis is on leveraging its strengths in tandem with human capabilities, emphasizing the collective potential of a harmonious collaboration between the two entities.